Tarihi Çevrede Ulaşım Stratejisi ve İlkeleri: Şirince Örneği / Transportation Strategy and Principles in Historical Environment: The Example of Sirince - Gülhan, Görkem (Journal of History Culture and Art Research, 2018)
ABSTRACT Throughout history, cities and transportation have been interacting. The types and volume of this interaction have diversified with the change over time in the types of transportation, vehicles and spaces. This relationship between transportation characteristics and settlement patterns has been shaped by the social, spatial and economic characteristics of history, and in this context has created new and different opportunities for interaction. Rapid and violent enlargement in cities after the industrial revolution and the establishment of links for new scales related to transport axes have separated street patterns in historical environments from the new urban dynamics. Historical environments could not be fully analyzed within this scale, and the applications directed towards the historical environment were designed to protect more. Historical urban centers have begun to be viewed as isolated and distressed areas, not as a stakeholder of the urban transport system. Issues such as the damage of the protection of the living spatial problems and the destruction of the historical environment have begun to be encountered. Troubles such as air/noise pollution, deterioration of urban image and vibration of vehicles caused damage to historical texture and brought together new planning approaches. There is a need for applications and approaches that will successfully integrate historic environments and transportation systems into the urban transport and land use fiction. In this study, the spatial structure and transportation structure of Selçuk-Sirince, which is a strong historical environment containing intensive transportation demands, is analyzed. Principles, strategies and approaches to overcome transportation problems have been developed. The approach is made in 3 categories as analysis, problem determination and strategy production. It has been determined that Sirince is experiencing spatial damage and that transportation problems are in both vehicular and pedestrian dimensions in conclusion a solution proposal is presented. ÖZ Tarih boyunca kentler ve ulaşım etkileşim içerisinde olmuştur. Bu etkileşimin türleri ve şiddeti, ulaşım türlerinin, araçların ve mekânların zaman içinde değişimi ile birlikte farklılaşmıştır. Ulaşım özellikleri ve yerleşim dokuları arasındaki bu ilişki tarihin sosyal, mekânsal ve ekonomik özelliklerine göre şekillenmiş ve bu bağlamda her dönemde yeni ve farklı etkileşim olanakları yaratmıştır. Sanayi devriminden sonra kentlerde yaşanan hızlı ve şiddetli genişleme, ulaşım aksları ile ilgili bağlantılarının yeni ölçekler için oluşturulması, tarihi çevrelerde yaşayan sokak dokularını yeni kent dinamiğinden ayrıştırmıştır. Yaşanan hızlı ve kontrolsüz büyümenin etkileri kentlerin ölçeğini yeniden belirlerken tarihi çevreler bu ölçek içerisinde tam olarak çözümlenememiş olup tarihi çevreye yönelik uygulamalar daha çok korumaya yönelik oluşturulmuştur. Tarihi kent merkezleri kentsel ulaşım sisteminin bir paydaşı olarak değil, izole ve ulaşım açısından sıkıntılı alanlar olarak görülmeye başlanmıştır. Yaşanan mekânsal sorunların çözümünde koruma olgusunun zarar görmesi ve tarihi çevrede tahribatlar oluşması türünde sorunlar ile karşılaşılmaya başlanmıştır. Hava/ses kirliliği, kent imgesinin bozulması ve taşıtlardan oluşan titreşimlerin tarihi dokuya zarar vermesi gibi sorunlar yeni planlama yaklaşımları arayışlarını beraberinde getirmiştir. Tarihi çevre ve ulaşım sistemlerini kentsel ulaşım kurgusuna başarı ile entegre edecek uygulama ve yaklaşımlara ihtiyaç duyulmaktadır. Bu çalışmada, yoğun ulaşım talebi içeren ve güçlü bir tarihi çevre niteliği olan Selçuk-Şirince Köyü’nün mekânsal yapısı ve ulaşım kurgusu analiz edilmiştir. Ulaşım sorunlarının çözümü ile ilgili ilkeler, stratejiler ve yaklaşımlar geliştirilmiştir. Anılan yaklaşım analiz, sorunların belirlenmesi ve strateji üretimi olmak üzere 3 kategoride yapılmıştır. Şirince’nin mekânsal tahribat yaşadığı, ulaşım sorunlarının hem taşıt hem yaya boyutunda olduğu tespit edilmiş olup çözüm önerileri sunulmuştur.